Islamic Legal Perspectives on Climate Justice: Integrating Environmental Ethics and Economic Responsibility - Zeynaddin Musennif Shabanov; Gulay Yusifli Elshad; Elshad Yusifov (Mabadi Iqtishad Al Islami, 2025)
This study explores Islamic legal perspectives on climate justice by integrating environmental ethics with economic responsibility within the wider framework of Sharia. Using a qualitative library research approach, it examines classical sources such as the Qur’an, Hadith, and uṣūl al-fiqh, alongside contemporary works on Islamic environmental ethics, sustainable development, and climate governance. The findings show that Islamic principles—including khalifah (stewardship), mīzān (balance), ‘adl (justice), and maslahah (public interest)—provide a strong ethical foundation for addressing climate change and preventing environmental corruption (fasād). The Maqāṣid al-Sharī‘ah, particularly the preservation of life, property, lineage, and the environment, support environmentally conscious policies and sustainable economic practices. Islamic finance instruments such as green sukuk and ESG-aligned investments further promote ecological responsibility. Overall, Islamic legal and economic traditions offer a comprehensive framework that links environmental sustainability with socio-economic equity, positioning Islamic thought as an important contributor to global climate justice discourse.